Zina (Adultery) in the Perspectives of Islamic Criminal Law and Indonesian Positive Law: A Comparative Analysis of Criminal Elements, Evidentiary Standards, and Penal Sanctions - Dini Aprilia Pasaribu; Salwa Suci Ramadhani; Afrialdy Fansyuri Hasibuan; Mahran Siregar (ISNU Sumatera Utara, 2024)
Zina is a criminal offense that receives significant attention in both Islamic Criminal Law and Indonesian Positive Law because it is closely related to the protection of morality, social order, and family institutions. The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code has introduced new legal developments regarding the regulation of adultery, making it important to compare its provisions with the concept of jarimah zina in Islamic Criminal Law. This study aims to analyze and compare the elements of the offense, evidentiary requirements, and criminal sanctions for zina from the perspectives of Islamic Criminal Law and Indonesian Positive Law. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through library research, including the examination of legislation, the Qur’an, Hadith, scholarly books, and relevant scientific journals. The findings reveal that Islamic Criminal Law classifies zina as a jarimah hudud, with clearly defined elements, evidentiary standards, and sanctions derived from Islamic legal sources. In contrast, Indonesian Positive Law regulates adultery through statutory provisions based on the principles of legality and modern criminal justice. The fundamental differences between the two legal systems are reflected in their evidentiary standards and forms of punishment. Nevertheless, both systems share a common objective of preserving public order, protecting individual dignity, and maintaining family integrity within society.